Methanobacterium alkalithermotolerans sp. nov., a novel alkaliphilic and hydrogen-utilizing methanogen isolated from an alkaline geothermal spring (La Crouen, New Caledonia). Issue 10 (19th October 2022) - Mei, Nan; Postec, Anne; Bartoli, Manon; Vandecasteele, Céline; Wils, Laura; Gil, Lisa; Monnin, Christophe; Pelletier, Bernard; Erauso, Gael; Quéméneur, Marianne
Abstract : An anaerobic, hydrogenotrophic methane-producing archaeon was isolated from an alkaline thermal spring (42 °C, pH 9.0) in New Caledonia. This methanogen, designated strain CAN T, is alkaliphilic, thermotolerant, with Gram-positive staining non-motile cells. Strain CAN T grows autotrophically using hydrogen exclusively as an energy source and carbon dioxide as the sole carbon source (without the requirement of yeast extract or other organic compounds). It grows at 20–45 °C (optimum, 45 °C) and pH 7.3–9.7 (optimum, pH 9.0). NaCl is not required for growth (optimum 0 %) but is tolerated up to 1.5 %. It resists novobiocin, streptomycin and vancomycin but is inhibited by ampicillin and penicillin, among other antibiotics. The genome consists of a circular chromosome (2.2 Mb) containing 2126 predicted protein-encoding genes with a G+C content of 36.4 mol%. Phylogenetic analysis based on the 16S rRNA gene sequence indicated that strain CAN T is a member of the genus Methanobacterium, most closely related to the alkaliphilic Methanobacterium alcaliphilum WeN4 T with 98.5 % 16S rRNA gene sequence identity. The genomes of strain CAN T and M. alcaliphilum DSM 3459, sequenced in this study, share 71.6 % average nucleotide identity and 14.0 % digital DNA–DNA hybridization. Therefore, phylogenetic and physiological results indicate that strain CAN T represents a novel species, for which the name Methanobacterium alkalithermotolerans sp. nov. is proposed, and strain CAN T (=DSM 102889 T = JCM 31304 T ) is assigned as the type strain.